Advances in smart grid power system network, control and security - Tomar, Anuradha; Kandari, Ritu (Academic Press, 2021)
"Advances in Smart Grid Power System: Network, Control and Security discusses real world problems, solutions, and best practices in related fields. The book includes executable plans for smart grid systems, their network communications, tactics on protecting information, and response plans for cyber incidents. Moreover, it enables researchers and energy professionals to understand the future of energy delivery systems and security. Covering fundamental theory, mathematical formulations, practical implementations, and experimental testing procedures, this book gives readers invaluable insights into the field of power systems, their quality and reliability, their impact, and their importance in cybersecurity. Includes supporting illustrations and tables along with valuable end of chapter reference sets Provides a working guideline for the design and analysis of smart grids and their applications Features experimental testing procedures in smart grid power systems, communication networks, reliability, and cybersecurity"--Publisher
Includes bibliographical references and index. - Online resource; title from PDF title page (Ebook Central, viewed April 1, 2021)
Keywords: Smart power grids; Smart power grids -- Communication systems; Smart power grids -- Security measures; Réseaux électriques intelligents; Réseaux électriques intelligents; Systèmes de communication; Réseaux électriques intelligents; Sécurité; Mesures